Kualitas Tidur Terhadap Tingkat Stres Pada Lanjut Usia Di Desa Mekar Jaya Sumatera Utara - Hasanah, Nur (Barongko: Jurnal Ilmu Kesehatan, 2024)
Sleep pattern disturbance is a condition where a person experiences a change in the quantity or quality of their rest pattern, causing discomfort and disrupting their activities. Increasing age in the elderly will basically be followed by changes in the normal sleep and rest patterns of the elderly. Stress is an unpleasant condition in an individual which can cause physical and psychological pressure on the individual. The aim of this research was to determine the level of stress and sleep quality in the elderly in Mekar Jaya Village. This research method uses a cross sectional research design where the population in this study is all elderly people in Mekar Jaya Village, totaling 157 elderly people. The sampling technique used Total Sampling Technique with inclusion criteria and exclusion criteria. The instruments used for stress levels and sleep quality used questionnaires. The results of the statistical test research with (p – 0.000 or p<0.05) show a value of p = 0.003 with Ho rejected and Ha accepted. The conclusion is that there is a significant relationship between stress levels and sleep quality in the elderly in Mekar Jaya Village.